2009
DOI: 10.1021/nl803830n
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Unintentionally Incorporated Nitrogen-Related Complexes in ZnO and GaN Nanowires

Abstract: We report the observation of unintentionally incorporated nitrogen-related complexes in ZnO and GaN nanowires grown by the catalytic vapor-phase transport method. In particular, our experimental findings from Raman scattering spectroscopy and mass-selected time-of-flight particle emission measurements suggest the presence of interstitial nitrogen molecules that are formed during the nanowire growth. These results may be relevant for many nanowire systems, emphasizing the necessity of more studies on unintentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 51 publications
1
34
0
Order By: Relevance
“…The NWs used in this study were synthesized by the vapor-liquid-solid method on Si/SiO 2 substrates with Au colloids as the catalysts [27]. A mixture of ZnO (Alfa Aesar, 99.999%) and graphite (Alfa Aesar, 99.9995%) powders in a quartz boat was used as the Zn source.…”
Section: Methodsmentioning
confidence: 99%
“…The NWs used in this study were synthesized by the vapor-liquid-solid method on Si/SiO 2 substrates with Au colloids as the catalysts [27]. A mixture of ZnO (Alfa Aesar, 99.999%) and graphite (Alfa Aesar, 99.9995%) powders in a quartz boat was used as the Zn source.…”
Section: Methodsmentioning
confidence: 99%
“…For N 2 accommodated parallel to the basal plane and c-axis in ZnO, we calculated a vibrational frequency of x 0 = 2191 cm À1 and 2010 cm À1 , respectively. Compared with nitrogen molecules in vacuum or air, the vibrational mode exhibits a pronounced shift of up to 382 cm À1 to smaller wavenumbers (Table I) single-crystal ZnO, 28 ZnO, and GaN nanowires 29 showed a vibrational mode located at x 0 = 2306 cm À1 . While Friedrich and Nickel 28 suggested that its microscopic origin is linked to the presence of N-complexes, Soudi et al 29 claimed that this local vibrational mode is due to molecular nitrogen.…”
Section: The Molecular Orbitals Of N 2 and N 2 O Inmentioning
confidence: 99%
“…We are planning further studies on more efficient nanoparticle formation and doping and the effects of sample preparation and treatment. We also wish to investigate the plasmonic properties of the nanoparticles, nanostructures 6 of ZnO, and the interface between the two, all of which may have important applications in electronic and photonic devices. Steve Langford is a senior research associate focusing on probing mechanisms of laser/materials interactions, including defect production and both surface and bulk modification of transparent materials.…”
Section: Continued On Next Pagementioning
confidence: 99%